2016
DOI: 10.3892/or.2016.5173
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression profile of lncRNA in endometrial carcinoma

Abstract: Endometrial carcinoma (EC) is the most common malignancy in women. Dispite its prevalence, the prognosis of endometrial carcinoma still relies on conventional histological type, grade and invasion information. Its morbidity is still increasing and the outcome is very poor. To the best of our knowledge, hormonal imbalance and/or molecular genetic alterations are the main cause of EC. However, the alterations of lncRNAs which accounts for approximately 4/5 of human transcripts are still poorly understood. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…It is involved in cell growth, proliferation, and differentiation, and some classes of its protein are involved in cancer development [24]. KIAA0087 is a noncoding RNA gene associated with endometrial and pancreatic cancers [25]. Also, a non-coding RNA gene, MGAT3 (Mannosyl (Beta-1,4-)-Glycoprotein Beta-1,4-N-Acetylglucosaminy ltransferase) is involved in the function and biosynthesis of glycoprotein oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in cell growth, proliferation, and differentiation, and some classes of its protein are involved in cancer development [24]. KIAA0087 is a noncoding RNA gene associated with endometrial and pancreatic cancers [25]. Also, a non-coding RNA gene, MGAT3 (Mannosyl (Beta-1,4-)-Glycoprotein Beta-1,4-N-Acetylglucosaminy ltransferase) is involved in the function and biosynthesis of glycoprotein oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of lncRNA and their role in defining EEC subgroups and their clinical aggressiveness must be defined further. Xu et al suggested that six lncRNAs may be the main regulators of endometrial carcinogenesis [ 38 ]. Xu measured a total of 172 lncRNAs and 188 mRNAs and reported that they were expressed differently in type I EC and the normal control samples [ 38 ].…”
Section: Competing Endogenous Rnas Mirna Lncrna Profiling Regulamentioning
confidence: 99%
“…Nevertheless, mounting evidence has emphasized the roles and clinical significance of non-coding RNAs and, in particular lncRNAs, among others in endometrial cancer (33,34).…”
Section: Discussionmentioning
confidence: 99%